The clandestinauts - Sievert, Tim, 1983- (Uncivilized Books, 2018)
"Hired to acquire the fabled Goblet of the Crimson Wizard, expert dungeoneering team, the Clandestinauts, enter the legendary Master Wizard's formidable fortress with visions of unimaginable treasure. That is until, like most journeys through the dreary depths of blood-soaked sepulchers, things don't go according to plan. Threats external and existential stand ready to test the frayed sinews that bind this team of bitter rivals." -- p.4 of cover.